Transcriptome and Metabonomics Analysis Revealed the Molecular Mechanism of Differential Metabolite Production of Dendrobium nobile Under Different Epiphytic Patterns - Li, Qingqing; Liu, Chaobo; Huang, Ceyin; Wang, Mufei; Long, Teng; Liu, Jingyi; Shi, Junhua; Shi, Junli; Li, Lin; He, Yuqi; Xu, De-Lin (Frontiers in Plant Science, 2022)
The cultivation medium of Dendrobium nobile has an effect on the contents of its main medicinal components, but the specific mechanism is still unclear. In this study, the callus, seedlings, rhizomes and leaves of D. nobile were sequenced for the PacBio SMRT sequencing. The 2-year-old steams were selected for the Illumina sequencing and metabolome sequencing to analyze the genetic mechanism of metabolic differences under different epiphytic patterns. As a result, a total of 387 differential genes were obtained, corresponding to 66 differential metabolites. Different epiphytic patterns can induce a series of metabolic changes at the metabolome and transcriptome levels of D. nobile, including flavonoid metabolism, purine metabolism, terpenoid backbone biosynthesis, amino acid metabolism and alpha-linolenic acid metabolic, and related regulatory genes include ALDH2B7, ADC, EPSPS-1, SHKA, DHAPS-1, GES, ACS1, SAHH, ACS2, CHLP, LOX2, LOX2.3, CYP74B2. The results showed that the genetic mechanism of D. nobile under different epiphytic patterns was different. In theory, the content of metabolites under the epiphytic patterns of Danxia stone is higher, which is more suitable for field cultivation.